A Review of Radiation Protection Standards for Workers in Hospital Radiology: A Narrative Literature Review - Yoshandi, Mohammad; Annisa (Sriwijaya Journal of Radiology and Imaging Research, 2023)
One of the goals of radiation protection is to prevent stochastic effects from occurring and to limit the chances of stochastic effects occurring to a limit value that is acceptable to soci ety. This literature review aims to describe radiation protection standards for workers in hospital radiology. To prevent non-stochastic effects, a limit of 0.5 Sv (50 rem) in 1 year was used for all tissues except the lens of the eye. For eyepieces, the recommended annual limit is 0.15 Sv (15 rem). This limit va lue is used either for radiation reception by a single tissue or for radiation rec eption by multiple organs. To limit stochastic effects, the annual effective equivalent dose (HE) limit for whole-body radiation reception is 50 mSv (5 re m). The radiation protection equipment that must be available at a radio diagnostic facility is a lead apron, thyroid shield, gonad protectors, gloves, Pb g oggles, and lead curtains. In conclusion, radiation protection equipment must be provided by radiology facility operators and used by radiation workers, especially radiologists and other competent doctors. Periodic inspection and st andardized maintenance of radiation shields must be carried out for the sake of public safety.